Are IPOs of different VCs different? - Tereza Tykvová; Uwe Walz (Goethe University Frankfurt, Center for Financial Studies (CFS), 2004)
This paper aims to analyze the impact of different types of venture capitalists on the performance of their portfolio firms around and after the IPO. We thereby investigate the hypothesis that different governance structures, objectives and track record of different types of VCs have a significant impact on their respective IPOs. We explore this hypothesis by using a data set embracing all IPOs which occurred on Germany's Neuer Markt. Our main finding is that significant differences among the different VCs exist. Firms backed by independent VCs perform significantly better two years after the IPO compared to all other IPOs and their share prices fluctuate less than those of their counterparts in this period of time. Obviously, independent VCs, which concentrated mainly on growth stocks (low bookto- market ratio) and large firms (high market value), were able to add value by leading to less post-IPO idiosyncratic risk and more return (after controlling for all other effects). On the contrary, firms backed by public VCs (being small and having a high book-to-market ratio) showed relative underperformance.
urn:nbn:de:hebis:30-10549
Keywords: G10; G14; G24; 330; Venture Capital; Initial Public Offerings; Long-Run Performance; Underpricing; Wertpapieremission; Risikokapital; Corporate Governance; Börsenkurs; Unternehmensentwicklung; Schätzung; Deutschland